Jeux vidéo : entreprises numériques au croisement du ludique et du narratif - Rémi Cayatte (Transatlantica)
This article is concerned with the evolution of the narrative tools implemented by different development studios over the past five decades. Its goal is to raise the question of the evolution of the nature of stories, and of the space devoted to these stories in video games. It appears that various trends arose over the years and led to the current situation of unification of these various trends and to the creation of games that proved themselves to be multi-narrative supports.